The Temperature Dependence of the Zeta Potential in Porous Media - Duy Thanh, Luong (VNU Journal of Science: Mathematics - Physics; Vol 33 No 4DO - 10.25073/2588-1124/vnumap.4090, 2017)
The measurements of the zeta potential of five consolidated samples including natural and artificial ceramic rocks saturated with 5.0×10 -3 M NaCl electrolyte at different temperatures have been reported. The zeta potential obtained in this work is always negative and increases in magnitude with increasing temperature for all samples (an average increase of the zeta potential of 0.4 mV/ o C in magnitude). The experimental results are in good agreement with previously published data. The experimental data is then explained by a theoretical model. It is shown that the model is able to reproduce the main trend of the experimental data from our work and from published articles.